PENGHAPUSAN MEREK CRISTALINE (GIE CRISTALINE) OLEH PT. PEPPER TREE INVESTAMA BERDASARKAN UNDANG-UNDANG NO. 20 TAHUN 2016 - Manihuruk, Stephanie Karin; Saly, Jeane Neltje (UNES Law Review, 2023)
Intellectual property rights are forms of human thought that are embodied in the form of works, works of art, designs and inventions that can be used in human life. The purpose of this study was to find out the lawsuit against the dispute over the brand mineral water product brand "CRYSTALINE" PT Pepper Tree Investama against GIE CRISTALINE and to find out the judge's decision by considering the law for violation of the brand dispute over the mineral water product brand "CRYSTALINE" PT Papper Tree Investama against GIE CRISTALINE according to envoy Number 47 PK/Pdt.Sus-HKI/2020. This research method uses normative juridical legal research methods. The approach method applied in this research is by law (statute approach) and case (case approach). The results of this study are that registered trademarks can be deleted by third parties and on the basis of the initiative and the judge's decision has rejected the plaintiff's claim in its entirety.